Radial and femoral access for interventional fellows performing diagnostic coronary angiographies: the LEARN-Cardiogroup II, a prospective multicenter study. Issue 11 (November 2018) - Omedè, Pierluigi; Bertaina, Maurizio; Cerrato, Enrico; Rubio, Lolo; Nuñez-Gil, Ivan; Gili, Sebastiano; Taha, Salma; Macaya, Carlos; Escaned, Javier; D'Ascenzo, Fabrizio
Abstract : Background: Safety and efficacy of radial and femoral access for coronary angiography performed by cardiology fellows remain to be evaluated. Methods: In this multicenter prospective study, cardiology fellows selected the access site (among femoral, right and left radial artery) for coronary angiography. All bleeding events related to the access site and all complications (a composite of all bleedings and artery occlusion) were the co-primary safety end points. Success for each access site, procedural and radiological times and single components of primary outcome were the secondary ones. Results: Overall, 201 patients were enrolled. Fellows chose right radial, left radial or femoral access in 164 (82%), 20 (10%) and 17 (8%) cases, respectively. All-cause bleedings were lower in radial cohort (4 vs. 19%; P  = 0.001) mainly driven by minor bleedings (4 vs. 18%, P  = 0.012). Also, overall complications were less frequent with the radial approach (18 vs. 30%, P  = 0.03) and radial artery occlusion did not differ between right vs. left side (4 vs. 5%, P  = 0.76). Procedural time (minutes) was similar between radial and femoral site (23 ± 9 vs. 22 ± 10, P  = 0.91), as well as time of X-ray exposure (6 ± 3 vs. 4 ± 2, P  = 0.11), DAP (Gy/cm 2 : 17 ± 11 vs. 18 ± 12, P  = 0.74) and amount of contrast medium (ml: 106 ± 81 vs. 84 ± 43, P  = 0.89). Success for access was significantly higher with radial artery (89 vs. 71%, P  = 0.004). Conclusion: Radial artery is the most exploited access by cardiologist fellows, leading to reduction in minor bleedings and higher success compared with femoral access. No differences in procedural time and radiation exposures were recorded. Abstract : Supplemental Digital Content is available in the text